Voluntary Carbon Offsets. Klimaschutz im Luftverkehr? - Eisenkopf, Alexander; Knorr, Andreas (Deutscher Verkehrs-Verl., 2009)
Der Markt für freiwillige Maßnahmen zur Kompensation von Treibhausgasemissionen, so genannte Voluntary Carbon Offsets (VCO), hat sich in den vergangenen Jahren rasant entwickelt. Während im Jahr 2000 nur vier Anbieter für CO2-Handelsplattformen existierten, wurden in einer Studie aus dem Jahr 2007 über 40 Organisationen gezählt, die die Möglichkeit eröffnen, durch Zahlungen für Kompensationsprojekte die Klimaneutralität insbesondere von Reiseaktivitäten sicherzustellen.

As a voluntary measure to compensate for greenhouse gas emission, "Voluntary Carbon Offsets" have enjoyed growing popularity, notably so in the case of air transport. The report shows that "Voluntary Carbon Offsets" do show notable shortcomings with regard to climate policy measures based on classic and purely economic terms. Of particular concern is the transparency of the basis used for calculations, the availability of suitable projects to deal with emission compensation, and the impact of incentives for dynamic efficiency. Generally speaking, efficiency-oriented climate protection politics ought not to rely on the efficacy of "Voluntary Carbon Offsets". Efforts should be directed towards more development, and the eventual adoption, of appropriate emission trading mechanisms. The inclusion of air transport - currently intended to be handled on a selective basis - in the European emission trading system is likely to burden this sector with a range of counterproductive side issues.
Voluntary Carbon Offsets air transport's contribution to climate protection?
Keywords: Verkehr; Luftverkehr; Umweltpolitik; Kohlendioxid; Emission; Umweltökonomie; Luftverkehrsmittel; Wirtschaftlichkeit; Klimaschutz; Treibhausgas; Emissionshandel; Emissionszertifikat; Kompensation